Attitude : develop a winning mindset on and off the court - Wright, Jay, 1961-; Sheridan, Michael, 1947 October 17-; Dagostino, Mark (Ballantine Books, 2017)
The head basketball coach at Villanova University outlines the leadership strategies he attributes to the successes of his NCAA championship team and how they can be adapted to enable personal and professional excellence.